Successful reperfusion in relation to the number of passes: comparing outcomes of first pass expanded Treatment In Cerebral Ischemia (eTICI) 2B with multiple-pass eTICI 3. (27th January 2022) - Bruggeman, Agnetha A E; Kappelhof, Manon; den Hartog, Sanne J; Burke, James F; Berkhemer, Olvert A; van Es, Adriaan C G M; van Zwam, Wim H; Dippel, Diederik W J; Coutinho, Jonathan M; Marquering, Henk A; Majoie, Charles B L M; Emmer, Bart J
Abstract : Background: Higher expanded Treatment In Cerebral Ischemia (eTICI) reperfusion scores after endovascular treatment (EVT) are associated with better outcomes. However, the influence of the number of passes on this association is unclear. We aimed to compare outcomes of single-pass good reperfusion (eTICI 2B) with multiple-pass excellent/complete reperfusion (eTICI 2C/3) in daily clinical practice. Methods: We compared outcomes of patients in the MR CLEAN Registry with good reperfusion (eTICI 2B) in a single pass to those with excellent/complete reperfusion (eTICI 2C/3) in multiple passes. Regression models were used to investigate the association of single-pass eTICI 2B versus multiple-pass eTICI 2C/3 reperfusion with 90-day functional outcome (modified Rankin Scale (mRS)), functional independence (mRS 0–2), per-procedural complications and safety outcomes. Results: We included 699 patients: 178 patients with single-pass eTICI 2B, and 242 and 279 patients with eTICI 2C/3 after 2 and ≥3 passes, respectively. Patients with eTICI 2C/3 after 2 or ≥3 passes did not achieve significantly better functional outcomes compared with patients with single-pass eTICI 2B (adjusted common OR (acOR) 1.06, 95% CI 0.75 to 1.50 and acOR 0.88, 95% CI 0.74 to 1.05 for 90-day mRS, and adjusted OR (aOR) 1.24, 95% CI 0.78 to 1.97 and aOR 0.79, 95% CI 0.52 to 1.22 for functional independence). Conclusions: Our results did not show better outcomes for patients who achieved eTICI 2C/3 in multiple, that is, two or more, passes when compared with patients with single-pass eTICI 2B. However, this concerns observational data. Further research is necessary to investigate the per-pass effect in relation to reperfusion and functional outcome.